NOCTUIDAE (INSECTA : LEPIDOPTERA) OF MUZAFFARNAGAR FROMUPPER INDO-GANGETIC PLAIN - RAJVANSHI, SHUBHIRA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
A survey conducted for the collection of Noctuidae from Upper Indo-Gangetic plain, Muzaffarnagar, in particular, the survey resulted into a record collection of 47 noctuid species represented by 36 genera and 13 subfamilies. The present attempt has been first of its type. Hampson (1892 & 1894) have used for determination of noucid species including Arctiidae and Lymphatidae as subfamilies of Noctuidae. The noctuids reported from Varanasi and Palamau ecosystems have also been compared with the noctuids recorded from Upper Indo-Gangetic plain ecosystem together with their food plants. The Catocalinae remain dominant and rich. Spodoptera lilura (Fabr.) assessed being recorded in all 3 ecosystems. Noteworthy, have been the determination of synonyms of the noctuid species, and revision of subfamily placement by British Museum.